THE INFLUENCE OF QUALITY MANAGEMENT SYSTEM ISO 9001: 2008 APPLICATION ON EMPLOYEE PERFORMANCE (A Case Study on PT. Apac Inti Corpora) - Nia Budi Puspitasari, Diana Puspitasari Rizka Amalia Kusumarini (USIM, THAMKAM, KHON KAEN, UMY, 2016)

(untitled)
PT. Apac Inti Corpora is an integrated textile company which has implemented Quality Management System (QMS) ISO 9001 of more than 10 years. By implementing the ISO, impact on the employee performance is not good. The 2014 production target of spinning and denim fabric was not achieved and there was a production delay. From literature, it is also known that quality culture can affect employee performance. So this study was conducted to determine the effect of ISO 9001 QMS application to the quality culture and employees performance. Application of ISO 9001 QMS itself can be divided into three dimensions, namely ISO certification planning, organizational commitment, and application procedures. Results of study concluded that application of ISO 9001 QMS directly influence the quality culture and indirectly influence positive effect on employee performance. Organizational commitment, procedures implementation and quality culture are known to directly affect employee performance, but there is no influence on the ISO certification planning. Improvements to do are improving application procedures, focusing employee work, conducting internal audits more quickly for production department, and establishing contracts cooperation with machinery spare parts suppliers. Nevertheless, the QMS ISO implementation, quality culture, and organizational performance have been perceived in a good category by respondents. Keywords : ISO 9001, quality culture, performance, Structural Equation Modelling (SEM)